Perilaku Konsumtif Penggunaan Online Shopping dan Sistem Pay Later dalam Perspektif Ekonomi Islam - Shadrina Afra Khairunnisa; Mita Chairunnisa Rahman; Chika Apriyanti; Dwi Octaviani Putri; Hisny Fajrussalam (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study analyzes and finds out the consumptive behavior of the community in using online shopping through the pay later system law in the perspective of Islamic economics in Indonesian society. This research was conducted through a quantitative survey method with the data analysis process analyzing respondents' answers to the distributed survey because this method reveals factual data based on the experiences of the respondents. This research was conducted quantitatively by conducting surveys and research data presented in the form of graphic images and accompanied by descriptions. The data analysis process is carried out by analyzing respondents' answers to the distributed survey because the method applied by the researcher will reveal data based on the reality of information according to the disclosure of respondents according to the circumstances experienced. The results of the study state that the law of the pay later system in an Islamic economic perspective depends on its use, whether it contains harm or not. The pay later system can be said to be haram if it contains things that are prohibited by Allah SWT, such as usury, gharar, and other harmful things. However, if the pay later system provides benefits, is relevant to the Islamic economy, and does not contain elements of harm such as usury, then the law is allowed.